2013
DOI: 10.3174/ajnr.a3651
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Angiographic Vascularity of Meningiomas with Dynamic Susceptibility Contrast-Enhanced Perfusion-Weighted Imaging and Diffusion Tensor Imaging

Abstract: BACKGROUND AND PURPOSE:The roles of DTI and dynamic susceptibility contrast-enhanced-PWI in predicting the angiographic vascularity of meningiomas have not been studied. We aimed to investigate if these 2 techniques could reflect the angiographic vascularity of meningiomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Our study demonstrated a significant positive correlation between the nCBF and angiographic vascularity, in keeping with the finding of the previous study, in which normalized cerebral blood volume obtained from dynamic susceptibility contrast-enhanced PWI was used. 17 Conventional angiography can provide some valuable information that may help in planning surgery. However, a non-negligible neurological complication rate of up to 1.3% has been previously reported, suggesting that special care needs to be taken in patient selection.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our study demonstrated a significant positive correlation between the nCBF and angiographic vascularity, in keeping with the finding of the previous study, in which normalized cerebral blood volume obtained from dynamic susceptibility contrast-enhanced PWI was used. 17 Conventional angiography can provide some valuable information that may help in planning surgery. However, a non-negligible neurological complication rate of up to 1.3% has been previously reported, suggesting that special care needs to be taken in patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…A neurointerventionist (Y.D.C., with 10 years of experience) and a neuroradiologist (T.J.Y., with 12 years of experience), who were blinded to ASL-PWI findings, reviewed the entire series of angiographic images and graded the degree of angiographic vascularity on the basis of previously reported criteria: Grade 0, none; Grade 1, minimal; Grade 2, moderate; and Grade 3, marked. 17 Interobserver differences were resolved by consensus. In cases of multiple feeders, the vascularity of the tumor as a whole was estimated by summing tumor stains observed in each selective angiography.…”
Section: Visual Assessment Of Angiographic Vascularity On Dsamentioning
confidence: 99%
See 3 more Smart Citations